Stimulus valence, episodic memory, and the priming of brain activation profiles in borderline personality disorder - Szczepaniak, Morgan; Chowdury, Asadur; Soloff, Paul H.; Diwadkar, Vaibhav A. (Psychological medicine, 2022)
Borderline personality disorder (BPD) is characterized by instability in affective regulation that can result in a loss of cognitive control. Triggers may be neuronal responses to emotionally valenced context and/or stimuli. 'Neuronal priming' indexes the familiarity of stimuli, and may capture the obligatory effects of affective valence on the brain's processing system, and how such valence mediates responses to the repeated presentation of stimuli. We investigated the effects of affective valence of stimuli on neuronal priming (i.e. changes in activation to repeated presentation of stimuli), and if these effects distinguished BPD patients from controls. Forty BPD subjects and 25 control subjects (age range: 18-44) participated in an episodic memory task during fMRI. Stimuli were presented in alternating epochs of encoding (six images of positive, negative, and neutral valence) and recognition (six images for 'old' v. 'new' recognition). Analyses focused on inter-group differences in the change in activation to repeated stimuli (presented during Encoding and Recognition). Relative to controls, BPD showed greater priming (generally greater decrease from encoding to recognition) for negatively valenced stimuli. Conversely, BPD showed less priming for positively valenced stimuli (generally greater increase from encoding to recognition). Plausibly, the relative familiarity of negative valence to patients with BPD exerts an influence on obligatory responses to repeated stimuli leading to repetition priming of neuronal profiles. The specific effects of valence on memory and/or attention, and consequently on priming can inform the understanding of mechanisms of altered salience for affective stimuli in BPD.